Le corps féminin à Casablanca : un reflet mouvant des rôles de genre ? - Leila Bouasria; Nezha Aidi (L’Année du Maghreb)
The standards of beauty change as societal expectations regarding the female body evolve. In this article, the body is regarded as the sum of physical characteristics and visible attributes, linked to anatomical norms, which meant to reflect an ideal of feminine beauty. Less attention is placed on these attributes themselves than on how they evolve in response to societal changes. A considerable influence is exerted by aesthetic, economic, and media norms, reshaping the perception of the female body. Women face contradictions: their bodies are expected to be desired and attractive while also feared and dreaded; they are supposed to be generous while staying within predefined boundaries. This article seeks to explore how the female body subtly reflects gender dynamics, the liberation of desire, tensions between the individual and the collective, and a growing aspiration for equality.Indeed, the evolution of women’s status, their presence within mixed spaces, and their access to employment and public education illustrate these changes. These transformations do not necessarily alter the female body but rather influence perceptions and bodily behaviors. For a long time, plumpness was a criterion of feminine beauty indicating privileged social status, while a supple body suggested lightness in movement and, by extension, moral looseness in a Maghrebian context where women were expected to be secluded to maintain the established patriarchal order. A curvaceous woman was considered beautiful because she was seen as capable of assuming all domestic responsibilities, whereas a less voluptuous woman did not meet prevailing beauty standards. The appeal of a certain body volume ultimately reflects the desire to conform to specific roles. It is true that access to public space had led to an interest in flexibility, combined with injunction to tone down an exuberant image. Fulfilling male demands regarding sexuality evokes a traditional erotic image; however, the public sphere demands a toning down of this image to adhere to social norms. Subject to male fantasies on one hand, and stigmatization on the other when it does not conform to gender stereotypes in the collective imagination, a new ideal of a “controlled body”, capable of adapting to social changes is gradually emerging in representations. It must be shaped and adapted to individual and collective requirements.Furthermore, difficulties in accessing the matrimonial market, prolonged celibacy, and the proliferation of intra- or extramarital intimate experiences, redefine the nature, formation, and expectations of couples, which are no longer solely focused on reproduction. Moroccan women, who are employed or financially autonomous, assert their right to reclaim their bodies through various aesthetic experiences to free themselves from societal constraints. Active women seek to distance themselves from patriarchal stereotypes, namely sexual availability, maternal dedication, and social subordination. Moroccan literature reflects the beginning of the liberation of female desire and pleasure from the taboo. Women increasingly demand equality in terms of emotional and sexual matters, leading to a growing interest in the consumption of bodily aesthetics, which is actually a liberation from certain intergenerational gendered logics, as well as those related to race and class.